Influence of co-depositor materials and modification of substrate on the formation of dendrites on the anode of a zinc-based secondary battery. (December 2020) - Homan, Bart; Quintero Pulido, Diego F.; ten Kortenaar, Marnix V.; Hurink, Johann L.; Smit, Gerard J.M.
Abstract: Dendrite formation poses serious problems in the operation of zinc-based batteries. Electrode material and electrolyte composition are known to have an influence on the dendrite formation. In this paper possible solutions for the reduction of dendrite formation at the anode of a zinc-based battery are studied. The electrochemical behaviour of various electrode materials and electrolyte compositions is researched. It is observed that the tested electrode materials have no significant impact on the reaction at the anode. However, significant reduction in dendrite formation are observed at various electrode materials. The largest reduction in dendrite formation is observed when SGL bipolar graphite is used as electrode material. Furthermore, using several analysis methods (CV, EIS, SEM) it is observed that the addition of low concentrations (around 10% of the main component concentration) of certain additives (MgBr2, MnSO4 ) to the electrolyte has no significant impact on the electrolyte reaction at the anode, but prevents the formation of dendrites. Finally, the changes in substrate material and electrolyte additive do not have significant influence on the over-all performance of the battery.